Chick Benetto’s Personality in For One More Day By Mitch Albom through Lacan’s Three-Stage Psychoanalysis - Yusuf, Adriansyah Maulana; Heriyati, Nungki (Mahadaya: Jurnal Bahasa, Sastra, Dan Budaya, 2025)
This Mitch Albom’s novel For One More Day explores Chick Benetto’s struggle with family trauma and identity crisis. This study aims to reveal how trauma, parental influence, and identity crises shape Chick’s psychological development via Lacanian psychoanalysis. Using qualitative textual analysis, we apply Lacan’s three orders – the Imaginary, Symbolic Order, and the Real – to trace Chick’s evolution. At the Mirror Stage, Chick forms an “Ideal-I” reflecting imagined wholeness. Disruptions in the Symbolic (a divorced father and broken home) shatter this ego, fueling Chick’s inferiority and identity crisis. Encountering the unsymbolizable Real (his father’s abuse, his mother’s loss) forces Chick to confront repressed trauma. Findings reveal how trauma and parental influence shape Chick’s narrative arc. We conclude that Lacanian analysis illuminates Chick’s journey from misrecognition to self-reconciliation, highlighting identity and resilience in the novel. Keywords: Jacques Lacan, Psychoanalysis, For One More Day, Chick Benetto